Heavy metals concentration in sediment and their bioaccumulation in several organisms in Benoa Bay and Lembongan Island, Bali, Indonesia - PUTU YUDI ADITYA PUTRI; RASTINA RASTINA; TRI PRARTONO; MEUTIA SAMIRA ISMET (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Putri PYA, Rastina, Prartono T, Ismet MS. 2024. Heavy metals concentration in sediment and their bioaccumulation in several organisms in Benoa Bay and Lembongan Island, Bali, Indonesia. Biodiversitas 25: 3230-3238. Human activities could be responsible for introducing heavy metals into coastal areas, and it can contaminate coastal waters such as the tourism area of Benoa Bay and coastal ecosystems of Lembongan Island, Bali, Indonesia. This study aimed to assess the extent of heavy metals on the sediment of those area and their accumulation rate in several marine organisms, including macro-algae (Ulva sp.), seagrass (Thalassia hemprichii), and sea urchin (Diadema sp.). Samples of surface sediments and marine organisms were collected at six stations for both areas and the presence of five heavy metals (Fe, Pb, Cd, Cu, and Cr) was determined using the AAS method. The concentration those metals varied significantly across the six stations. The geo-accumulation index showed that the sediment has been contaminated by Pb and Cd. The ecological risk of heavy metals contamination in Benoa Bay was apparently higher compared to that in Lembongan Island. Marine organisms in Benoa Bay also significantly accumulated heavy metals than those observed in Lembongan Island. Bioconcentration factor (BCF) shows that Cd, Cr, and Pb were the most accumulated heavy metals in marine organisms (BCF>1). It, therefore, suggest that future studies of the bioavailability of heavy metals and exploration the varying capacities of marine organisms are required. Such important information can be used to predict the accumulation of heavy metals in human bodies, and the possibly daily consumption of marine organisms caught from Benoa Bay and Lembongan Island waters.